Overview of Artificial Intelligence Applications in Chinese Medicine Therapy. (17th March 2021) - Feng, Chuwen; Zhou, Shuoyan; Qu, Yuanyuan; Wang, Qingyong; Bao, Shengyong; Li, Yang; Yang, Tiansong
Abstract : To evaluate the importance of AI technologies in modernizing traditional Chinese medicine (TCM) therapy, this article presents the systematic review of the relevant literature and explains the beneficial effects of AI technology on the TCM treatment outcomes from the experience of famous and veteran Chinese medicines, including acupuncture, Tui Na massage, and Qigong practitioners. This study also focuses on the urgent necessity to apply AI technologies to develop therapeutic models on the theme "treating the disease before it happens." Furthermore, the study also discusses the major bottlenecks and future prospects for the development of intelligent TCM treatment strategies.